Culture for Self-Reliance: Building the Foundation of the Grogol Cultural Village Initiative through a Culture-Based Rural Development Approach - Rina Widiastuti; Faizatush Sholikhah; Erlyna Nour Arrofiqoh (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
Culture-based village development has become an important strategy in achieving village self-reliance and strengthening local identity. Kalurahan Grogol, located in Kapanewon Paliyan, Gunungkidul Regency, is an area endowed with rich artistic expressions, traditions, and cultural heritage. However, these cultural assets have not been managed systematically, resulting in incidental and fragmented cultural activities. The 2025 Community Service Program of Universitas Gadjah Mada was implemented to establish the foundation of a Cultural Village Initiative through a culture-based rural development approach. The program addressed two main issues: the absence of a cultural masterplan and the lack of structured cultural preservation programs. The implementation methods included the formulation of a cultural masterplan, capacity building for cultural actors, establishment and activation of art studios, digitalization of cultural publications, and continuous mentoring over a six-month period. The results indicate several strategic achievement indicators, including the completion of the Grogol Cultural Village Masterplan, high community participation reaching 83.2% in training on studio management, traditional costume (adibusana), and ceremonial protocol (pranata adicara), the reactivation of three art communities—gejlog lesung, children’s karawitan, and young traditional dancers—and the revival of two cultural festivals, namely the Dakon Festival and Nguri-uri Kabudayan. Furthermore, the digitalization of cultural activities through the village website and TikTok platform has increased the visibility of cultural and artistic activities in Kalurahan Grogol. A notable finding regarding the low level of Javanese script literacy among the younger generation constitutes an important consideration for future program development. Overall, the program successfully strengthened community engagement in cultural activities and established a solid foundation for the designation of Kalurahan Grogol as a Cultural Village. These findings demonstrate that culture-based rural development, particularly in Kalurahan Grogol, can serve as an effective strategy to enhance social cohesion, local identity, and the socio-economic resilience of rural communities.